1971
DOI: 10.1021/ma60024a017
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Benzene through Poly(γ-benzyl L-glutamate)

Abstract: Permeability of benzene through polyfy-benzyl L-glutamate) (PBLG) film was found to be dependent on the solvent used for casting the membrane. Thin films of PBLG were cast from methylene chloride and benzene solutions. Permeability of benzene (liquid) through these membranes was measured at different concentrations of benzene, using heptane as diluent. Although the solubility coefficient of the film cast from benzene was only -~18% higher than that of the film cast from methylene chloride (densities being iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Permeability of Na + and K + Ions to Cast Film. Some papers , on the transport properties of small molecules through synthetic polypeptides of rodlike, α-helical structure have been published. The studies on poly( n -alkyl- l -glutamate) 21,22 indicate that the diffusion of small molecules in polypeptide occurs through the side-chain region between helices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability of Na + and K + Ions to Cast Film. Some papers , on the transport properties of small molecules through synthetic polypeptides of rodlike, α-helical structure have been published. The studies on poly( n -alkyl- l -glutamate) 21,22 indicate that the diffusion of small molecules in polypeptide occurs through the side-chain region between helices.…”
Section: Resultsmentioning
confidence: 99%
“…Some papers 21,22 on the transport properties of small molecules through synthetic polypeptides of rodlike, R-helical structure have been published. The studies on poly(n-alkyl-L-glutamate) 21,22 indicate that the diffusion of small molecules in polypeptide occurs through the side-chain region between helices. Moreover, biomembranes consist of a continuous nonpolar hydrocarbon matrix from the phospholipid bilayer substantially impermeable to most polar substances and protein molecules capable of reversibly binding specific substrates and of transporting them across the membrane even against a concentration gradient.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of these very thin grafted layers can be tuned very easily by functionalization of the glutamic acid monomer unit. Numerous LB studies indicated the applicability of polyglutamates in chemical sensors 12 and membranes for transport of ions, 13,14 electrons, 15,16 and other small molecules 17,18 to mimic biological functions. The optical activity of many polyglutamates 19 can lead to applications in the fields of waveguides, 20 data storage, 21,22 and nonlinear optics.…”
mentioning
confidence: 99%
“…The properties of these very thin grafted layers can be tuned very easily by functionalization of the glutamic acid monomer unit. Numerous LB studies indicated the applicability of polyglutamates in chemical sensors and membranes for transport of ions, , electrons, , and other small molecules , to mimic biological functions. The optical activity of many polyglutamates can lead to applications in the fields of waveguides, data storage, , and nonlinear optics. , Recently, Whitesell and Chang published the polymerization of alanine NCAs initiated by amine-functionalized gold substrates, producing highly ordered polymeric films with α-helices oriented nearly perpendicular to the surface.…”
mentioning
confidence: 99%